2008
DOI: 10.7863/jum.2008.27.3.425
|View full text |Cite
|
Sign up to set email alerts
|

Spherical Tissue Sampling in 3-Dimensional Power Doppler Angiography

Abstract: Spherical 1-cm3 sampling of ovarian tissue with 3D ultrasound power Doppler angiography is a sensitive and promising approach to differentiate between ovarian tumors and normal ovaries. It opens the possibility to implement objective computerized positioning, standardized comparison, and analysis of ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 32 publications
3
24
0
Order By: Relevance
“…66 Similar results were reported by Kudla et al but using a 1 cc spherical sampling. 67 The only study that has not shown differences in 3D PD indexes between benign and malignant ovarian tumors was reported by Ohel et al 68 However, the series was too small (only 17 cases) and the methods used were not fully explained.…”
Section: Adnexal Tumorsmentioning
confidence: 97%
See 1 more Smart Citation
“…66 Similar results were reported by Kudla et al but using a 1 cc spherical sampling. 67 The only study that has not shown differences in 3D PD indexes between benign and malignant ovarian tumors was reported by Ohel et al 68 However, the series was too small (only 17 cases) and the methods used were not fully explained.…”
Section: Adnexal Tumorsmentioning
confidence: 97%
“…69 This may be solved using 1 cc sphere. 67 Several studies have shown that, whatever the approach used, manual or spherical sampling, reproducibility is high between observers. [69][70][71] Regarding to the contribution to diagnosis of ovarian cancer, Geomini et al reported a multicenter prospective study concluding that the use of 3D ultrasound significantly improves the prediction of malignancy as compared to 2D ultrasonography.…”
Section: Adnexal Tumorsmentioning
confidence: 99%
“…It is believed that vascularization index (VI) represents the amount of vessel in the examined volume, flow index (FI) shows the flow intensity, and vascularization-flow index (VFI) reflects the combination of both [27]. A number of studies examined the suspicious areas in adnexal masses and found that 3D PD indices were significantly higher in those that are malignant [29][30][31][32]. It is worth mentioning that there is no agreement among experts on which specific index is better at diagnosing malignancies, or which cut-off value provides the best sensitivity and specificity.…”
Section: Oncologymentioning
confidence: 99%
“…102 Kudla et al proposed using a 1-cc spherical sampling and also found that 3D-PDA indices were significantly higher in malignant tumors. 103 Only one study has not shown differences in 3D-PD indices between benign and malignant ovarian tumors. 104 However, the series was too small (only 17 cases).…”
Section: Three-dimensional Ultrasound In Adnexal Pathologymentioning
confidence: 99%
“…105 Several studies have shown that whatever the approach used, manual or spherical sampling, reproducibility is high between observers. 101,103,105,106 Two prospective studies have shown that 3D-PDA may significantly decrease the false-positive rate of malignancy in vascularized solid and cystic-solid adnexal masses without decreasing significantly sensitivity. 107,108 The results of these studies are summarized in Table 6.…”
Section: Notesmentioning
confidence: 99%